Water Quality Characteristics of Jonge Telaga (Doline Pond) as Water Resources for the People of Semanu District Gunungkidul Regency - M. Widyastuti (Indonesian Journal of Geography, 2017)
Abstract Doline ponds (telaga) have an important role as one of water resources in karst areas, especially during dry seasons in Gunungkidul. Recently, the doline ponds are facing various environmental problems, i.e. steadily decreasing water storage, water loss, and degrading water quality. The research aims to determine the characteristics of Jonge Telaga which include the continuity of flow, utilization, pollution sources, physical water quality (temperature, EC,TDS, TSS, and turbidity), chemical water quality (pH , NO2, NO3, NH4, PO4, BOD , COD, and detergent), and biological water quality (total coliform). In order to determine the characteristics of Jonge Telaga, the research was conducted using a survey method, i.e., observing the continuity of flow and measuring physical, chemical, and biological water quality. Initially, the water was sampled purposively based on the area and the depth of this doline pond. The qualitative description of the results shows that Jonge Telaga is a closed perennial doline pond, whose main pollution source comes from domestic activities, such as bathing and washing. According to the Governor Regulation of the Special Region of Yogyakarta Number 20 Year 2008 on Water Quality Standards, Jonge Telaga meets all of the water quality criteria, except the temperature and detergent, for a Class II water.